Exploring the Students’ Perception on Peer Feedback in Writing Class: A Study of Undergraduate Students in English Department of UNP - Tanjung, Yusra Handesca Putra; Sari, Senorica Yulia (Universitas Negeri Padang, 2024)
This research aimed to the perception of the students in essay writing class about peer feedback in english department of UNP. The study focuses on student perceptions, the role of peer feedback, and a comprehensive literature review on writing skills. Employing a quantitative methodology, data on students' perceptions of peer feedback in writing classes were collected through a questionnaire based on Farrah (2012). Using descriptive quantitative methods, the findings reveal that participants possess a positive perception of peer feedback's contribution to the enhancement of critical thinking, writing abilities, creativity, motivation, and the creation of a relaxed learning environment. The research suggests that peer feedback serves as a valuable tool in fostering the improvement of writing abilities among undergraduates